2013
DOI: 10.1111/add.12294
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hazardous drinking on suicide among working-age Russian males: an individual-level analysis

Abstract: Hazardous drinking substantially increases the risk of suicide among working-age Russian males, with nearly half of all suicides attributed to this drinking pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
0
13
2
Order By: Relevance
“…case-control study indicated that hazardous drinking substantially increases the risk of suicide among working-age Russian males, with nearly half of all suicides attributed to this drinking pattern [22]. Aggregate-level studies also reveal an association between population level drinking and suicide rates in Russia and Belarus [23][24][25][26][27][28][29][30].…”
Section: Acta Psychopathologica Issn 2469-6676mentioning
confidence: 99%
“…case-control study indicated that hazardous drinking substantially increases the risk of suicide among working-age Russian males, with nearly half of all suicides attributed to this drinking pattern [22]. Aggregate-level studies also reveal an association between population level drinking and suicide rates in Russia and Belarus [23][24][25][26][27][28][29][30].…”
Section: Acta Psychopathologica Issn 2469-6676mentioning
confidence: 99%
“…). His paper aims at assessing the impact of hazardous drinking on suicide among working‐age Russian males . Previous research suggests that the relationship between alcohol and suicide varies, in that it is especially strong in drinking cultures characterized by frequent binge drinking.…”
Section: Declarations Of Interestmentioning
confidence: 99%
“…Upon receiving the invitation to reply, then reading the commentary, I did not know how to respond. Norström's comments are mainly laudatory and his discussion of my study's limitations is fair. I had no rejoinder.…”
mentioning
confidence: 93%